Crayfish shell biochar for methyl violet adsorption: Equilibrium and kinetic studies - Azrul Nurfaiz, Mohd Faizal; Chew, Hui Wen; Nicky Rahmana, Putra; Ahmad Syahmi, Zaini; Agi, Augustine Aja; Abu Hassan, Nordin; Muhammad Abbas, Ahmad Zaini (Elsevier Ltd, 2025)
This work was aimed to establish the equilibrium and kinetics of methyl violet removal onto crayfish shell biochars. The biochars were prepared through pyrolysis at 500, 650 and 800 ℃℃ for 1.5 h. The biochars were labelled as CS500, CS650 and CS800, respectively. All biochars are highly mesoporous with CS650 exhibits a higher surface area of 665 m2/g. The adsorption results are tied up with the physiochemical properties of biochars. The CS800 displays the maximum dye capacity at 1079 mg/g. The performance of biochars is given in the order of, CS800 > CS650 > CS500. The equilibrium of methyl violet adsorption was best described by modified Langmuir isotherm, while the kinetic data obeyed pseudo-second-order model. The removal of methyl violet is governed partly by precipitation onto crayfish shell biochars. To conclude, the crayfish shell is a potential feedstock of biochar for dye wastewater treatment.